THE RELATIONSHIP OF CHILDREN'S KNOWLEDGE ABOUT CONSUMING CARIOGENIC FOODS WITH THE STATUS OF DENTAL CARRIES IN CLASS V STUDENTS OF SDN LAMPEUDAYA ACEH BESAR - Suryani, Linda; Rosmawar , Hetty (Jurusan Kesehatan Gigi Poltekkes Kemenkes Aceh, 2022)
Abstract Cariogenic foods are foods that contain carbohydrates that can cause tooth decay if consumed continuously. Lack of knowledge about dental and oral hygiene can also cause various diseases in the oral cavity, one of which is dental caries. Dental caries is a disease that destroys tooth structure starting from the tooth surface extending to the pulp. The purpose of this study was to determine the relationship between children's knowledge about consuming cariogenic foods and dental caries status in fifth grade students at SDN Lampeudaya Aceh Besar. This research is analytic with cross sectional design. The sampling technique used was Total Sampling, namely all students of class V at SDN Lampeudaya Aceh Besar, totaling 31 people. The results showed that of the 31 fifth grade students at SDN Lampeudaya Aceh Besar, who had knowledge about consuming cariogenic foods in the unfavorable category were 19 respondents (61.3%), with dental caries status in the moderate category as many as 9 respondents (29.0 %), then the obtained value (P value = 0.018). Data analysis used is univariate analysis and bivariate analysis using chi-square statistical test with 0.05. Based on the results of the study, it can be concluded that there is a relationship between children's knowledge about consuming cariogenic foods and dental caries status in fifth grade students at SDN Lampeudaya Aceh Besar. It is expected for students to reduce the consumption of cariogenic foods that are sweet and sticky which can damage teeth, for parents and teachers to be able to monitor the type of food consumed by children, and for health workers to be able to provide counseling about the impact and influence of cariogenic foods on dental caries . Keywords: Knowledge, Children, Cariogenic food, Dental caries.